A Facile Method for a Quantitative Study of the Mechanical Force Impact on Fabric Dye Loss During Domestic Washing. Issue 4 (30th April 2016) - Cai, Guoqiang; Guo, Liyun; Ge, Huayun; Wang, Jiping
Abstract: Mechanical abrasion force may be the most important cause for dye loss of fabric in low temperature washing using bleach‐free detergent during domestic washing. In this work, a facile method was developed to investigate the effect of mechanical abrasion force on the dye loss of fabrics. The amount and composition of abraded dyes were quantitatively determined by UV–Vis and HPLC methods, respectively. Results showed that the abraded dyes consisted of fiber bonded dyes and unfixed dyes, and bonded dyes with fractured short fibers took up a larger proportion after several washings. Mechanical abrasion force also facilitated desorption of unfixed dyes and hydrolysis of covalent bond. Meanwhile, the K/S value decreased quickly and surface morphology of fabric was seriously damaged in strong mechanical abrasion condition.